Eccentric exercise physiology and application in sport and rehabilitation - Hoppeler, Hans 1948- (Routledge research in sport and exercise science, 2015)
"Eccentric muscle contraction, during which a muscle lengthens while under tension, is a fundamental process of human movement but a surprisingly under-researched area of exercise science. Evidence suggests that training programmes which incorporate both eccentric and concentric contractions can result in greater strength gains than concentric contractions alone, and this clearly has important implications for training and rehabilitation in sport and health. In Eccentric Exercise, leading international sport scientist Hans Hoppeler introduces the fundamental physiology and pathophysiology of eccentric muscle work, and explores the key applications of eccentric exercise in sport, rehabilitation and health. The book examines the molecular mechanisms responsible for tissue and organismic adaptations and discusses eccentric muscle-related pathology, specifically delayed onset muscle soreness. It assesses the use of eccentric exercise training in the treatment of certain disease states such as chronic obstructive pulmonary disease, heart insufficiency and sarcopenia, while a concluding chapter points to open research questions, shows the limits of the available data and highlights problems with current exercise modalities. This book is important reading for all sport and exercise scientists, clinicians working in rehabilitation, and high-level strength and conditioning coaches and trainers"--Provided by publisher.